Significance of selected morphological and histopathological parameters of colon tumors as prognostic factors of cancer spread - Zbigniew Krzysztof Kamocki; Natalia Anna Wodyńska; Joanna Laura Żurawska; Konrad Piotr Zaręba (Turkish Journal of Gastroenterology, 2019)
Background/Aims: The identification of prognostic factors of metastatic development is one of the most important issues in colorectal cancer (CRC) research. The aim of this study was to determine the usefulness of colon tumor characteristics, including location, circumferential location, histological type, and histological grade, as predictors of metastases. Materials and Methods: To identify potential predictors of CRC spread, we analyzed data of 191 patients who had undergone surgery for colon tumors. We searched for potential associations between the location in the right or left colon, circumferential location, histological type, and histological grade (G-parameter) of colon tumors and the incidence of lymph node and distal metastases. The analysis was based on Pearson’s chi-square (χ2) test with a statistical significance of p<0.05. Results: Lymph node metastases were found in 100 patients, including 44 patients with synchronous liver metastases. Lymph node involvement was detected in 43 (52.4%) patients with right-sided and in 57 (52.3%) patients with left-sided tumors (p=0.984). Liver metastases were detected in 19 (23.17%) patients with right-sided colon tumors and in 25 (22.9%) patients with left-sided tumors (p=0.969). Lymph node and liver metastases were found in 60 (47.6%) and 24 (19.0%) patients with annular tumors, respectively (p=NS), and these were found on the mesenteric side in 75.0% (n=30) and 20.0% (n=8) patients (p=0.004) and on the antimesenteric side in 47.6% (n=10) and 48.0% (n=12) patients (p=0.044), respectively. Conclusion: The circumferential location of primary colon tumors is a significant predictor of their metastatic potential. The mesenteric location of the tumor is predisposed to lymphatic spread, whereas the antimesenteric location predicts hematogenous spread. Cite this article as: Kamocki ZK, Wodyñska NA, Zurawska JL, Zareba KP. Significance of selected morphological and histopathological parameters of colon tumors as prognostic factors of cancer spread. Turk J Gastroenterol 2017; 28: 248-53.